Evaluasi mutu susu segar dari peternak berbeda di provinsi Lampung sebagai bahan baku keju [The quality of fresh milk from different farmers in Lampung as a raw material for cheese] - Neti Yuliana; Iyan Indrawan; Chandra Utami Wirawati; Sumardi Sumardi (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
The objective of this study was to evaluate the quality of fresh cow’s milk from different farmers in Lampung Province as a raw material for cheese in view of the Indonesian National Standard SNI 31411 (2011) regulation.  Twelve fresh milk samples from four different districts (Tanggamus, Metro, Gisting, and Pesawaran) were evaluated by estimation of total protein and fat, pH, alcohol test, total plate count, antibiotic residues, and sensory. The result of the study revealed that the samples had protein and fat ranged from 2.44 to 3.90 %, and from 3.48 to 4.73% (wet basis) respectively.  The fresh milks had normal sensory and pH, negative of alcohol test, and free from antibiotic residues. Total microbes were detected in log 5-6 CFU/ml.  Majority of the samples screened met the Indonesian National Standard and could be used as a raw material for cheese making.  Keywords:  cheese,  fresh milk quality, Lampung province, SNI 31411,